Migration, Livelihood Strategies, and Agricultural Outcomes: A Gender Study in Rural China1. (13th November 2018) - Tong, Yuying; Shu, Binbin; Piotrowski, Martin
Abstract: In this study we examine whether the gender composition of migrants from rural households affects household economic strategies and agricultural productivity, which is the fundamental economic activity for rural Chinese. Using data from the 2010 and 2012 Chinese Family Panel Studies, this study treats households as the unit of analysis. Our results show that households with migrants are less likely to engage in agricultural activities or operate small businesses than households with no migrants. However, households with female migrants are less likely to engage in agricultural activities to a greater extent than those with male migrants, whereas the latter pose an obstacle to running small family businesses. This suggests that women may have to shoulder the burden of agricultural work when men migrate, whereas having male migrants from the households hampers households from engaging in local nonagricultural activities. Finally, although having male migrants who have left does not significantly discourage households from continuing agricultural activities, it does reduce agricultural productivity.